ANALGETIC ACTIVITY OF CEP-CEPAN (Saurauia cauliflora DC.) LEAVES EXTRACT - Emil Salim; Cut Fatimah; Dewi Yul Fanny (Universitas Syiah Kuala, 2017)
Abstract. Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. The people who live in Karo use several types of plants to relieve pain, one of which is cep-cepan (Saurauia cauliflora DC.) The leaves of this plant traditionally used to treat gastrointestinal disorders. There is no scientific evidence about analgetic effect of the leaves. Thus, this study aimed to determine the potential effect of the ethanolic extract of cep-cepan leaves as an analgesic. Fresh Cep-cepan leaves were dried in a drying cabinet at 40°C. Furthermore, the water content of the powdered dried leaves was determined using azeotropic distillation method. Phytochemical screening was carried out to determine chemical groups contained in the dried leaves. Plant extraction was done by maceration method using ethanol 96%. Analgesic effect of the extract was evaluated by observing respon time of mices to infrared as pain inducer. Mices were grouped into six categories, they were: vehicle, antalgin 65 mg/kgBW, and extracts at the dose of 500 mg/kgBW, 250 mg/kgBW, 125 mg/kgBW, 62,5 mg/kgBW, all were administered orally. The data were analayzed using ANOVA followed by LSD. Results showed that the dried leaves contained flavonoids, alkaloids, tannins, anthraquinone glycosides and steroids/triterpenoids. The water contain of the dried leaves was 5,3%. The analgesic test results showed the extract at the dose of 250 mg/kgBW had strong analgesic effect similar to that of 500 mg/kgBW and antalgin 65 mg/kgBW.Keywords: analgetic, antalgin, cep-cepan, leave, saurauia cauliflora.